Investigating the effectiveness of livelihood capital in reducing re-poverty risk: an empirical analysis of policy withdrawal and income structures in rural China - Fan, Yipin; Ning, Jing; Qin, Hong (Frontiers in Environmental Science, 2023)
In the context of China's comprehensive poverty alleviation efforts, this study explores the differences in the re-poverty risk between households that have been lifted out of poverty before and after policy withdrawal, as well as the sensitivity of different family types to their livelihood capital. The study used data from 45,141 out-of-poverty households in Yucheng County, Henan Province, from 2016 to 2020 and combined the poverty vulnerability theory and short-fall risk method to evaluate the re-poverty risk. The Tobit model was used to explore the influence of livelihood capital on the re-poverty risk. The study found that the overall re-poverty risk is 1.13%, which increases to 18.09% after direct poverty alleviation policy is withdrawn. The risk of working families is significantly lower than farming families. All kinds of livelihood capital significantly reduce the re-poverty risk, with natural capital playing the most significant role. For different family types, the marginal contribution of financial capital to reducing the re-poverty risk is relatively larger in working households, while that of natural capital is larger in farming households. Specifically, labor capacity, arable land area, local leaders, and loans have a more significant inhibitory effect on the re-poverty risk. These findings provide valuable insights for formulating policies related to increasing household income and preventing the occurrence of re-poverty.